USE OF STATISTICAL CONTROL CHARTS FOR MONITORING THE QUALITY OF FLOUR - Tekić, Dragana (Journal on Processing and Energy in Agriculture, 2020)
The use of statistical quality control in the production and storage processes significantly enhances the overall quality of products. Although various techniques are used for quality monitoring purposes, control charts are considered of paramount importance. In this paper, the ash and moisture contents of the wheat flour type 500 were analyzed using descriptive statistics. Consequently, the control charts for the variations in and the mean values of the parameters considered were created. The control charts obtained for the mean parameter values show that the flour production process was in control relative to both parameters considered, exhibiting only random variations. However, the control charts obtained for the variability in the parameter values considered show special variations, the causes of which require further research in order to maintain the satisfactory quality of flour production.